Frictions to Political Competition and Financial Openness - Aristotelis Boukouras; Kostas Koufopoulos (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
In this paper we present a political economy approach in order to explain the degree of financial openness for an economy. In the model, entrepreneurs, who may have good or bad projects, vote for policies, which are proposed by selfi sh politicians. Two political frictions (ideological adherence and a super- majority requirement) impair political competition and lead to equilibria, where politicians receive corruption bribes. Furthermore, the model implies a non-monotonic relationship between financial openness and corruption and a positive relationship between financial openness and government size. Some of the model predictions are consistent with empirical findings while other predictions have not beeen tested yet.
Keywords: G21; G28; H32; P16; P43; 330; corruption; fi nancial openness; ideology; politicians